2016
DOI: 10.5114/hpr.2016.57681
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a factor in differentiating strategies of coping with stress used by physical education students

Abstract: health psychology report · volume 4(3), 6 original article background Students are exposed to numerous stressors associated with their integration into their university education, their relationships with friends, and anxiety about the future. Given that stress may be related to university students' academic performance, understanding the coping strategies used by students may be important in facilitating a positive transition to a university setting. The aim of this study was to determine the gender-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
3
14
2
1
Order By: Relevance
“…According to our results, seeking for help, actions directed to causes, self-instructions, and communicating feelings and seeking for social support are coping strategies associated positively with women. These results are contrary to previous studies [ 57 ] but they might reflect stable cultural differences because our results are consistent with prior studies with a Spanish population [ 56 ]. Negative associations are interesting as well.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…According to our results, seeking for help, actions directed to causes, self-instructions, and communicating feelings and seeking for social support are coping strategies associated positively with women. These results are contrary to previous studies [ 57 ] but they might reflect stable cultural differences because our results are consistent with prior studies with a Spanish population [ 56 ]. Negative associations are interesting as well.…”
Section: Discussioncontrasting
confidence: 74%
“…Women tend to regulate their stress through social support strategies, while men use more planning and positive reevaluation when coping with stress [ 56 ]. A study revealed that men obtained higher results in active coping strategies while women were more inclined to use avoidance oriented strategies—like distraction and behavioral disengagement [ 57 ]. On the contrary, men tend to “forget about it” in order to regain control, while women “talk about it” when dealing with stress [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result could be explained by the fact that women rely on strategies associated with seeking support more often than men do, which has been confirmed by previous research [33,34]. Thus, concentrating on forming interpersonal relations through looking for instrumental and emotional support seems more natural to women, which is in line with the results of female students in a study conducted at a sports university [35]. It is possible that, for this reason, women assess the threats more realistically and do not feel the need to underestimate them in order to gain social approval.…”
Section: Discussionsupporting
confidence: 84%
“…As with secondary school students, women tended to use NEG negative strategies (Sigmund, Kvintová, Dostálová, 2013). Guszkowska's research results (2016) have shown that men prefer choosing management strategies, while women prefer focus-seeking strategies, both emotional and material, and put more emphasis on emotions and avoiding solutions (Guszkowska, 2016). The meaning in the life of secondary school students is not a negligible part of their lives, as according to the research by Eun-hyeCho (2014), meaning in life is an important precursor of adapting to the conditions of the secondary school and in dealing with stressful situations.…”
Section: Discussionmentioning
confidence: 99%